STUDI EKSPERIMENTAL PERILAKU STRUKTURAL LANTAI KACA LAMINASI TERHADAP BEBAN LENTUR - Nugraha, Widi; Triwibowo, Hari; Subrata, Budi (Direktorat Bina Teknik Jalan dan Jembatan, 2024)
The development of laminated glass with enhanced ductility compared to standard glass presents promising opportunities for its utilization as load-bearing structural components, notably in floors and beams. Its application as bridge flooring has gained widespread acceptance across construction projects worldwide. Despite this, understanding laminated glass floor behavior remains limited due to its recent emergence in the construction sector. This study aims to investigate the structural response of laminated glass floors to vertical bending loads through bending tests conducted in a laboratory setting. Four samples were tested, including three with two layers of laminated glass and one with three layers, all using the same thickness of glass and interlayer, which is 12 mm and 1.5 mm, respectively. Vertical compressive loads were applied at the floor span center, with deformation measured incrementally. Test results show that all laminated glass floor specimens can withstand loads greater than the design load, with ductility reaching up to 2,23, showcasing post-failure ductile behavior and gradual bending failure conducive to safe evacuation. These findings significantly advance our comprehension of laminated glass in bridge construction, paving the way for innovative structural designs. Keywords: laminated glass, structural floor, bending test, ductility, stiffness